Money, e-money and consumer welfare - Francesco Carli; Burak Uras (Bank of Finland, 2022)
We develop a micro-founded monetary model to inquire the role of a privately provided e-money instrument for household consumption smoothing and welfare. Different from fiat money, e-money users pay electronic transaction fees, but in turn e-money reduces spatial separation frictions and enables risk-sharing. We characterize the conditions that promotes e-money to be Pareto improving and the conditions when e-money reduces its users' welfare - despite for the consumption-smoothing it induces. We calibrate our model for the context of M-Pesa in Kenya and conduct a quantitative analysis. Since our quantitative analysis reveals a limited role for privately provided e-money, we recommend the optimality of e-money regulation.
Keywords: E41; E44; G23; O11; 330; E-Money; M-Pesa; Risk-Sharing; Welfare; Monetary Policy